Psychological impact and health-related quality of life of patients in hemodialysis treatment - Rivadeneira Arias, Sara Angélica (2026)
This study examines the relationship between psychological impact and health-related quality of life in patients diagnosed with chronic kidney disease after one year of hemodialysis treatment. A descriptive, cross-sectional, and correlational research design was employed, involving a sample of 30 patients aged 26 to 68 years who received care at the Surmedial Dialysis Center in Guayaquil, Ecuador, during October 2024. Data were collected using the Hospital Anxiety and Depression Scale (HADS) and the Kidney Disease Quality of Life instrument (KDQOL SF-36). Data analysis was performed using Microsoft Excel and SPSS version 29.0. The findings indicate that 43.3% of the participants were male and 56.7% were female, with a mean age of 53 years. A total of 3% of patients presented symptoms consistent with an anxiety disorder, while 1% exhibited symptoms of a defined depressive disorder. The overall quality-of-life score averaged 61% (SD = 7.8), which is considered moderately satisfactory. A strong negative correlation was observed between psychological variables and quality of life (rs = –.750, p < .001). These results suggest that, in the absence of significant emotional disturbances, patients tend to report higher levels of quality of life. Furthermore, the study confirms the association between psychological impact and quality of life, identifying physical functioning as the most affected domain throughout the year of hemodialysis treatment.